Toxic trans‐crotonaldehyde in mitochondria intercepted by oxyresveratrol contributing to anticancer. Issue 7 (23rd April 2019) - Su, Yanbin; Sun, Chengyu; Chen, Yan; Liu, Shichang; Jing, Ning; Li, Shuxin
Abstract: The aim of this study was to explore how the toxic trans ‐crotonaldehyde (TCA) in mitochondria or aldehyde dehydrogenase (ALDH) at different pHs was intercepted by oxyresveratrol (Oxy‐Res) contributing to anticancer. Ultraviolet–visible (UV–vis) spectroscopy and Raman spectroscopy were employed. UV–vis spectra showed that the Oxy‐Res red shifted the peak of the toxic TCA from 316 nm to 325 nm, while the peaks of the Oxy‐Res shifted from 329 nm with 290 nm and 300 nm to 325 nm with 303 nm. In the mitochondria, the Oxy‐Res blue shifted the peaks of the toxic TCA from 325 nm with 303 nm to 321 nm with 301 nm. Raman spectra revealed that the Oxy‐Res caused shifting of the CHO of the toxic TCA from 1, 689 cm −1 to 1, 671 cm −1 with band decline. The CC of the toxic TCA at 1641 cm −1 was split into 1, 639 cm −1 and 1, 642 cm −1 with band decline. The bands of the Oxy‐Res at 1634 cm −1, 1, 617 cm −1, and 1, 595 cm −1 disappeared. In the mitochondria, the CC of the toxic TCA at 1641 cm −1 splitting disappeared. In ALDH, with the decrease of pH from 7.8 to 6.5, the CHO of the toxic TCA did not red shift from 1, 689 cm −1 to 1, 674 cm −1 up to pH 6.5. There was no change in the CC of the toxic TCA at 1640 cm −1 in ALDH at different pHs. The conclusion of the study was that the CHO of the toxic TCA was intercepted by the Oxy‐Res under the action of ALDH in the mitochondria, particularly at pH 7.8. © 2019 IUBMB Life, 2019